Effects of Clinical Pharmacist Intervention in a Saudi ICU: A Prospective, Cross-Sectional Study (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Given their contributions to better patient outcomes, medication safety, and lower drug cost, critical care pharmacists are especially prepared to play a major role within the critical care interdisciplinary team in managing the therapeutic element. Consequently, this research set out to evaluate the ICU clinical pharmacist interventions' frequency, kind, and effect, as well as the acceptability of these interventions by the doctors who provide them. The research was prospective and cross-sectional in nature. Over the course of six months, from April 1, 2023, to October 1, 2023, data was collected daily from a minimum of 380 interventions. This research covered all patients hospitalized to the intensive care unit at  Saudi Arabia throughout the specified time frame. Over the duration of the 6-month trial, 120 patients had a total of 500 interventions. Of these, 490 (98%) had physician approval for clinical pharmacist treatments. The majority of the recommendations (34.8%, or 174 out of 500) were related to safety concerns; among these, 48.27%, or 48 out of 174, were for medication cessation owing to extended duration, while 30.46%, or 53 out of 174, were for renal dosage modification. Coming up as a close second, another therapeutic intervention involving indication made up 22.8% (114/500). A total of 124 interventions, or 24.8 percent of the total, had some kind of cost-related component, according to the study's findings on cost-saving treatments. The results of this research showed that clinical pharmacists have the potential to improve quality treatment for critically ill patients and lower healthcare expenditures. Furthermore, it provides helpful information on the incorporation of clinical pharmacists in intensive care units, particularly in areas with limited resources.